THE FORGOTTEN : ACHIEVING SUSTAINABLE FISHERIES THROUGH THE EMPOWERMENT OF LOCAL WISDOM - Parsaulian, Baginda (Jakarta Technical University of Fisheries, 2024)
To understand the impact of culture on the economy, it is important to know the values and cultural norms that exist and have been applied by individuals in their economic activities. Fisheries sector also has several attributes that can be developed to create sustainability scenarios that have not yet been studied in West Pasaman district, West Sumatra province, Indonesia. This study aimed to demonstrate the potential of local wisdom as a valuable asset for fisheries sustainability. The research was conducted between January 2023 and June 2023 in West Pasaman Regency, West Sumatra Province, Indonesia, using RAPFISH and Participatory Prospective Analysis. The study identified key factors essential for achieving sustainable fisheries. The community of West Pasaman has a rich history of local fishing knowledge that can be fully utilised to achieve sustainability in the future. The crucial role of customary rules and local wisdom is highlighted. It is important to note that this knowledge should be taken into account in any efforts to achieve fisheries sustainability.